Identificação de graus de ansiedade à matemática em estudantes do ensino fundamental e médio: contribuições à validação de uma escala de ansiedade à matemática - Mendes, Alessandra Campanini (Universidade Federal de São Carlos, 2012)
The learning of mathematics has been characterized by aversion due to several failures in trying to learn its contents. Besides the traditional difficulties of learning mathematics, such as dyscalculia and acalculia, possibly related to organic and developmental disorders, the international literature has highlighted a new field of research: the mathematics anxiety. A phenomenon characterized by a specific set of unpleasant physiological reactions as well as cognitive and behavioral components which occur in the presence of simple or complex mathematical stimuli and contingencies of learning mathematics, or in contexts that require the use of mathematical repertoires. In Brazil, however, there are few studies about the identification of different degrees of math anxiety in students with different educational levels. In the analyzes of this study it was observed that the distribution of student responses is a normal distribution, which allowed the testing of medium and correlational tests. In addition, we observed a Cronbach's alpha coefficient, with a value of 0.900, which indicates that the instrument used is consistent. Thus, this study had as first objective to identify different degrees of math anxiety in elementary school students Cycle II (6th to 9th grade) and High School (1st, 2nd and 3rd grade) - correlating the variables gender, age, grade, public and private schools. The second objective was to identify which items of the scale typically generated high levels of anxiety, listed by the students. In Spearman correlation analysis, the results indicated a significant difference between the variables period (p = 0.005 and r = 0.084) and education system (p = 0.001 and r = -0.104) and there was no significant correlation between total scores and the variables age (p = 0.188 and r = -0.040), gender (p = 0.178 and r = -0.040), grade (p = 0.282 and r = -0.032), educational level (p = 0.503 3 r = 0.020). In the Student s t test and Anova, the analysis indicated a significant difference between the average of students responses in the variable education system (p = 0.001) and period (p = 0.018). No significant differences in the variables: gender (p = 0.104), instructional level (p = 0.476), grade (p = 0.154), age (p = 0.064). The results of the chi-square test indicated that high levels of anxiety occurred in 12 out of 24 scale situations and these situations indicated punishment or not, which involves the teaching methodologies as well as the individual learning of mathematics.
Keywords: Psicologia; Escala de ansiedade à matemática; Matemática - estudo e ensino; Aprendizagem; Ansiedade à Matemática; Estudantes do Ensino Fundamental e Ensino Médio; Mathematics anxiety; Mathematics anxiety scale; Teaching and learning of mathematics; Elementary and secondary students; CIENCIAS HUMANAS::PSICOLOGIA